HUBUNGAN POSITIF MODAL DAN SISA HASIL USAHA - Ady Soejoto, ; Iis Kresnawati Sutarjo, (Pendidikan Ekonomi, 2010)
The objective of the present study was to investigate the relationship between the capital and divident of the members of  KPRI Aneka Usaha Pusat Veterinaria Farma Surabaya. The study was associative research, using Spearman Rank Correlation. The data colletcion techniques were interview and documentation. The result of the study revealed that there was a significant positive association between the capital and divident. The capital and divident of KPRI Aneka Usaha Pusat Veterinaria Farma Surabaya stepped up every year because of the increasing savings and participation of the members.